Historiography of literary articles in the journal Allpanchis Phuturinqa - Manco Huambachano, Paul Martin (2024)
The current panorama of research on oral literatures -particularly Quechua and Aymara- is related to different disciplines, such as philosophy, sociology, anthropology or ethnography; or rather, it cannot do without them. The interest of this historiographical article is centred on explaining the functions that the publication of literary articles in the journal Allpanchis Phuturinqa, a publication very often related to the interest in knowledge that the social sciences develop on the basis of the culture and customs of the Andean people, fulfilled and continue to fulfil. The objective is to detail the what before the how; therefore, the articles of the magazine that collaborate with Peruvian literary criticism are presented and how they are combined with the different critical productions of literary interest throughout the years in which the research of Allpanchis Phuturinqa has been published.